Miller syndrome (postaxial acrofacial dysostosis): further evidence for autosomal recessive inheritance and expansion of the phenotype. Issue 10 (October 1991) - Ogilvy-Stuart, A L; Parsons, A C
Abstract : A sibship with postaxial acrofacial dysostosis syndrome (Miller syndrome) is reported. In addition to the characteristic facial and limb defects, previously undescribed anomalies, including midgut malrotation, gastric volvulus, and renal anomalies, are recorded.